Perilaku Etika Bisnis Dalam Meningkatkan Kualitas Kinerja Karyawan pada CV Khazha Vision - Cindy Fredicia Putri; Putri Dasti S Harahap; Yolanda Citra; Agustiawan (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This study aims to analyze the application of business ethics to CV Khazha Vision in improving the quality of employee performance. With descriptive qualitative methods, data were collected through interviews and direct observation in the field. The results of the study show that the principles of business ethics such as fairness, autonomy, honesty, and respect for individuals are applied consistently in companies. These principles create an inclusive work environment, increase employee motivation, and encourage productivity. In addition, the company maintains open communication, provides training, and respects the freedom of employees to take the initiative as long as it is in accordance with the organization's rules. The implementation of good business ethics not only strengthens employee loyalty but also improves the company's reputation, thereby supporting sustainable business growth.